Low utilisation of bronchoscopy to assess COVID-19 respiratory infection: a multicenter experience. Issue 1 (23rd July 2021) - Mahmood, Kamran; Abbott, Matt; Van Nostrand, Keriann; Bechara, Rabih; Gonzalez, Anne V; Brucker, Amanda; Green, Cynthia L; Polage, Christopher R
Abstract : Objective: For the diagnosis of COVID-19, the yield of nasopharyngeal (NP) swabs is unclear, and bronchoalveolar lavage (BAL) is obtained to confirm the diagnosis. We assessed the utilisation of bronchoscopy for COVID-19 diagnosis in a multicenter study and compared the diagnostic yield of BAL versus NP swabs. Methods: This retrospective study included all patients who were admitted with clinical presentation concerning for COVID-19 and underwent BAL from 1 March to 31 July 2020 at four tertiary care centres in North America. We also compared concordance of BAL with NP swabs for diagnosis of COVID-19 infection. Results: Fifty-three patients, with clinical suspicion for COVID-19 and admitted for respiratory failure, underwent bronchoscopy to collect BAL for SARS-CoV-2 testing. During the same period, 2039 bronchoscopies were performed on patients not infected with COVID-19. Of 42 patients with NP swabs and BAL collected within ≤7 days, 1 was NP swab negative but positive by BAL for SARS-CoV-2 (n=1/42 (2.4%)). Across a wide array of testing platforms, the overall agreement between NP swabs and BAL results was 97.6% (95% CI: 93.0% to 100%) with Cohen's k of 0.90 (95% CI: 0.69 to 1.00). The sensitivity, specificity, positive and negative predictive values of NP swabs compared with BAL were 83.3% (95% CI: 53.5% to 100%), 100%, 100% and 97.3% (95% CI: 92.1% to 100%), respectively. Conclusions: BAL was used infrequently to assess COVID-19 in busy institutions. NP swabs have a high concordance with BAL for COVID-19 testing, but negative NP swabs should be confirmed with BAL when clinical suspicion is high.